Rab3 Superprimes Synaptic Vesicles for Release: Implications for Short-Term Synaptic Plasticity - Schlüter, Oliver M. (J Neurosci, 2006)
Presynaptic vesicle trafficking and priming are important steps in regulating synaptic transmission and plasticity. The four closely related small GTP-binding proteins Rab3A, Rab3B, Rab3C, and Rab3D are believed to be important for these steps. In mice, the complete absence of all Rab3s leads to perinatal lethality accompanied by a 30% reduction of probability of Ca(2+)-triggered synaptic release. This study examines the role of Rab3 during Ca(2+)-triggered release in more detail and identifies its impact on short-term plasticity. Using patch-clamp electrophysiology of autaptic neuronal cultures from Rab3-deficient mouse hippocampus, we show that excitatory Rab3-deficient neurons display unique time- and frequency-dependent short-term plasticity characteristics in response to spike trains. Analysis of vesicle release and repriming kinetics as well as Ca(2+) sensitivity of release indicate that Rab3 acts on a subset of primed, fusion competent vesicles. They lower the amount of Ca(2+) required for action potential-triggered release, which leads to a boosting of release probability, but their action also introduces a significant delay in the supply of these modified vesicles. As a result, Rab3-induced modifications to primed vesicles causes a transient increase in the transduction efficacy of synaptic action potential trains and optimizes the encoding of synaptic information at an intermediate spike frequency range.